The DNA Damage Response: Implications on Cancer Formation and Treatment - Khanna, Kum Kum; Shiloh, Yosef (Springer Netherlands : Imprint: Springer, 2009)
The book The DNA Damage Response: Implications on Cancer Formation and Treatment brings together a great collection of review articles. The articles have been written by a group of experts who have a deep knowledge of the recent advances in the fields of DNA damage signalling and repair and their implications in carcinogenesis. The book is divided into chapters that deal with the elaborate surveillance system and repair mechanisms used by cells to suppress mutagenic lesions to avoid cancer. It provides snapshots of: * current understanding of DNA damage signalling, * cell cycle checkpoints, * some of the major DNA repair pathways, * functional links between DNA damage, * genomic instability and cancer, * implications of DNA damage for the development of new treatment modalities for cancer.